Implementasi Sikap Kolaboratif dan Multikultural dalam Kepemimpinan pada Integrasi dan Penataan Transportasi Umum “JAK LINGKO” di DKI Jakarta - Kurnia Rheza Randy Adinegoro (Universitas Sebelas Maret, 2022)
Jakarta is one of the big cities in Indonesia which is the center of government and economy of the country. The burden that Jakarta has is certainly more than other big cities, this is also directly proportional to the problems it faces. From the classic problems from the past, flooding, economic inequality, waste management to traffic jams in Jakarta. As a special province led by the Governor, Jakarta through its local government continues to seek solutions to the various problems in it. The role of leadership certainly cannot be separated from the process of unraveling this tangled thread. One way to solve the solution is with a collaborative leadership in multiculturalism. This style was carried out by Anies Baswedan as the governor of Jakarta in the context of solving transportation problems by being labeled with the name Jak Lingko. Jak Lingko integrates various modes of transportation by means of the government collaborating with transportation service providers in Jakarta.